Clicking for friendship: social network sites and the medium of personhood - Lee, Daniel B.; Goede, Jessica; Shryock, Rebecca (MedieKultur: Journal of media and communication research, 2010)
Social networking sites such as MySpace and Facebook depend on familiar social resources, including language, reading/writing and established semantic constructs such as personhood, privacy and friends. However, the use of computers, the Web 2.0 platform, and the latest networking software are revolutionising how “personhood” and “friendship” are produced by communication. We refer to the media theory of Niklas Luhmann to identify specific differences in how communication is organised and reproduced on networking sites. The electronic medium appears to be changing the way participants selectively construct and bind expectations of personhood and communicative ties to themselves and others. Using software available on the Web, users confront each other as digital bodies, as participants in communication, available for friendship within a new “ether of interactivity”.